2006
DOI: 10.1111/j.1440-1843.2006.00972.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of symptomatic large pleural effusions first diagnosed more than 30 days after coronary artery bypass graft surgery

Abstract: The incidence of symptomatic newly developed large pleural effusions first diagnosed at more than 30 days post CABG was 3.1%. Those who were diagnosed between 30 and 90 days post CABG tended to have exudative effusions, whereas those diagnosed more than 90 days post CABG often had left ventricular impairment and transudative effusions. Most of these effusions settled with conservative management and did not recur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 6 publications
1
19
0
1
Order By: Relevance
“…Morbidity and mortality rates were 17.6% and 0%, respectively, with the most common morbidity being congestive heart failure, transient ischemic attack, and atrial fibrillation. Peng et al (8) found 11/356 (3%) symptomatic post-CABG PEs. Late PEs (n=6) compared to early PE (n=5) had lower levels of LDH and lower ejection fraction, supporting congestive heart failure as aetiology.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Morbidity and mortality rates were 17.6% and 0%, respectively, with the most common morbidity being congestive heart failure, transient ischemic attack, and atrial fibrillation. Peng et al (8) found 11/356 (3%) symptomatic post-CABG PEs. Late PEs (n=6) compared to early PE (n=5) had lower levels of LDH and lower ejection fraction, supporting congestive heart failure as aetiology.…”
Section: Resultsmentioning
confidence: 98%
“…The present review included two case-series study including ≥4 patients (2,5), 7 retrospective analytical studies (3,4,(7)(8)(9)(10)(11), and one observational study (6) but no randomized controlled trials (RCTs). The score of the level of evidence according to the criteria of Centre for Evidence Based Medicine (CEBM) (12) was low.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations